Nonlinear d'alembert equation in the pseudo-euclidean space $R_{2,n}$ and its solutions - Yuryk, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the nonlinear D'Alembert equation in the pseudo-Euclidean space $R_{2,n}$ and construct new exact solutions containing arbitrary functions.